Tabut: Muharram Observances in the History of Bengkulu - R. Michael Feener (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 1999)
Tabut is the name given to the commemoration of Muharram as it is observed in Bengkulu, Indonesia. The basic traditions connected with its observance have their origins in Muslim India. However the Tabut has, over the course of its development in Bengkulu, absorbed and incorporated various local elements. Recently the